Co-inoculation With Rhizobacteria and Mycorrhizae Can Improve Wheat/Faba Bean Intercrop Performance Under Field Conditions - Raklami, Anas; Bechtaoui, Noura; Tahiri, Abdel-ilah; Slimani, Aiman; Bargaz, Adnane; Meddich, Abdelilah; Oufdou, Khalid (Frontiers in Agronomy, 2021)
The current challenges of climate changes and demographic expansion have imposed increasing awareness about innovation in sustainable agricultural practices. Farming practices like intercropping have many benefits in terms of nutrient use and yield stability. Improving the performance of intercropping systems by the application of beneficial microorganisms (rhizobacteria and/or mycorrhizae) constitutes a promising strategy. In this regard, this study aimed to assess the effect of inoculation with beneficial microorganisms on wheat as monocrop or intercrop with faba bean, using three inoculation treatments: (i) inoculation with rhizobacteria (ii) inoculation with mycorrhizae, (iii) inoculation with the rhizobacteria-mycorrhizae consortium, and (iv) a control treatment consisting of uninoculated plants. Results showed that rhizobacteria-mycorrhizae co-inoculation under intercropping system improved plant dry weight, spikes weight of wheat by 375% and 162% respectively compared to uninoculated intercropped wheat. The thousand-seed weight was improved by 86% in intercropped wheat intercropped and inoculated with the rhizobacteria-mycorrhizae consortium. Furthermore, higher P and N concentrations were observed in shoots and spikes of wheat intercropped with faba bean, and this increase was also observed in response to inoculation with the rhizobacteria-mycorrhizae consortium in terms of P in shoots and spikes (by 74 and 18%) of intercropped wheat. In addition, intercropped wheat has significantly accumulated sugar in the seeds for all inoculation treatments (except inoculation with mycorrhizae). Overall, these findings revealed that intercropping and inoculation yielded better suggesting that intercropping combined with the application of beneficial microorganisms, such as rhizobacteria and mycorrhizae, have the potential to improve overall crop yield.